LEADERSHIP STYLE AND ITS INFLUENCE ON THE IMPLEMENTATION OF COMMUNICATION FUNCTIONS IN BUSINESS COMMUNICATION (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. The article sets out topical issues related to the influence of leadership style on the implementation of communication functions in business communication. In particular, such a multifaceted process of interaction between people as communication is studied. It is realized in different forms and manifests itself in different formats. It is noted that the successful implementation of business communication is possible only with mastered communication skills because it involves interaction between people in the joint process of problem solving in achieving a specific professional goal.The purpose of the article. The purpose of the article is to determine the relationship between leadership style and the degree of implementation of the functions of business communication in business communication/Results. The content and functions of business communication are revealed. The characteristics are given and main determinants of leadership styles are defined according to the classification by K. Levin, who distinguishes authoritarian, democratic and liberal leadership styles. It is proved that the personality of a chief gives business communication a certain stylistic color and, depending on personal traits and established views and the gained experience, a chief chooses certain ways and methods of business communication to achieve a defined aim. The correspondence between management style and degree of realization of functions of business communication has been found based on our own observations where the characteristics such as «fully realized» («F»), «partially realized» («P») and «difficult to implement (almost not implemented)» («D») were used as a measure of function of business communication. It is proposed to use a formula that allows to indicate the number of business communication functions for each of the leadership styles. These functions are implemented to a certain extent (fully, partially, difficult). The analytical expression of such a formula is determined for each of the considered leadership styles (authoritarian, democratic and liberal).Conclusiоns. Based on the obtained formulas, it has been concluded the democratic style of leadership is the most acceptable and effective regarding the possibility of implementing the business communication functions because this style allows fully implement all functions of business communication.
Keywords: business communication, communication, communication functions, leadership style, role interaction.